Application and accuracy of ultrasound-guided resections of tongue cancer. (October 2022) - de Koning, Klijs J.; van Es, Robert J.J.; Klijn, Reinoud J.; Breimer, Gerben E.; Willem Dankbaar, Jan; Braunius, Weibel W.; van Cann, Ellen M.; Dieleman, François J.; Rijken, Johannes A.; Tijink, Bernard M.; de Bree, Remco; Noorlag, Rob
Highlights: Ultrasound provides good overview of the tongue tumour's extent and deep margin. Ultrasound-guided surgery leads to a significant increase in free margin status. Ultrasound-guided surgery halves the need for local adjuvant radiotherapy. An 8 mm margin on ex-vivo US prevents histopathological < 5 mm margins in 76%. Abstract: Objectives: Surgical removal of squamous cell carcinoma of the tongue (SCCT) with tumour-free margin status (≥5 mm) is essential for loco-regional control. Inadequate margins (<5 mm) often indicate adjuvant treatment, which results in increased morbidity. Ultrasound (US)-guided SCCT resection may be a useful technique to achieve more adequate resection margins compared to conventional surgery. This study evaluates the application and accuracy of this technique. Methods: Forty patients with SCCT were included in a consecutive US cohort. During surgery, the surgeon aimed for a 10-mm echographic resection margin, while the tumour border and resection plane were captured in one image. Ex-vivo US measurements of the resection specimen determined whether there was a need for an immediate re-resection. The margin status and the administration of adjuvant treatment were compared those of with a consecutive cohort of 96 tongue cancer patients who had undergone conventional surgery. A receiver operating characteristic analysis was done to assess the optimal margin of ex-vivo US measurements to detect histopathologically inadequate margins. Results: In the US cohort, the frequency of free margin status was higher than in the conventional cohort (55% vs. 16%, p < 0.001), and the frequency of positive margins status (<1 mm) was lower (5% vs. 15%, respectively, p < 0.001). Adjuvant radiotherapy was halved (10% vs. 21%), and the need for re-resection was comparable (10% vs. 9%). A cut-off value of 8 mm for ex-vivo measurements prevented histopathologically inadequate margins in 76%. Conclusion: US-guided SCCT resections improve margin status and reduce the frequency of adjuvant radiotherapy.